RiboScreenTM Technology Delivers a Ribosomal Target and a Small-Molecule Ligand for Ribosome Editing to Boost the Production Levels of Tropoelastin, the Monomeric Unit of Elastin - Wimmer, Bjoern; Schernthaner, Jan; Edobor, Genevieve; Friedrich, Andreas; Poeltner, Katharina; Temaj, Gazmend; Wimmer, Marlies; Kronsteiner, Elli; Pichler, Mara; Gercke, Hanna; Huber, Ronald; Kaefer, Niklas; et al. (International journal of molecular sciences, 2024)
Elastin, a key structural protein essential for the elasticity of the skin and elastogenic tissues, degrades with age. Replenishing elastin holds promise for anti-aging cosmetics and the supplementation of elastic activities of the cardiovascular system. We employed RiboScreenTM, a technology for identifying molecules that enhance the production of specific proteins, to target the production of tropoelastin. We make use of RiboScreenTM in two crucial steps: first, to pinpoint a target ribosomal protein (TRP), which acts as a switch to increase the production of the protein of interest (POI), and second, to identify small molecules that activate this ribosomal protein switch. Using RiboScreenTM, we identified ribosomal protein L40, henceforth eL40, as a TRP switch to boost tropoelastin production. Drug discovery identified a small-molecule hit that binds to eL40. In-cell treatment demonstrated activity of the eL40 ligand and delivered increased tropoelastin production levels in a dose-dependent manner. Thus, we demonstrate that RiboScreenTM can successfully identify a small-molecule hit capable of selectively enhancing tropoelastin production. This compound has the potential to be developed for topical or systemic applications to promote skin rejuvenation and to supplement elastic functionality within the cardiovascular system.
Keywords: tropoelastin; Elastin; elastin; Tropoelastin; ribozomální proteiny; Ribosomes; Ligands; lidé; ligandy; Small Molecule Libraries; Humans; Ribosomal Proteins; ribozomy; knihovny malých molekul